Multiple retransmission strategy‐based HARQ for MIMO systems with acknowledgment bundling. Issue 8 (1st April 2014) - Park, Sangjoon
Abstract : A new hybrid automatic repeat request (HARQ) scheme is proposed for multiple‐input multiple‐output (MIMO) systems when the acknowledgment (ACK) bundling is applied for packet retransmissions. In the proposed HARQ scheme, both Chase combining (CC) and incremental redundancy (IR) are utilised for a retransmission request, and the proposed HARQ scheme is called a multiple retransmission strategy‐based HARQ (MRS‐HARQ). During the reception process of the MRS‐HARQ, IR packets obtain signal‐to‐noise ratio gains using the extended detection with CC packets and the improved IR packets are utilised to eliminate the interference from the CC packets. This sequential reliability improvement allows the MRS‐HARQ to decrease the occurrence of the deficient transmissions, and the proposed MRS‐HARQ can achieve an improved error performance and throughput over the conventional CC‐based and IR‐based HARQ schemes with the ACK bundling.